2021
DOI: 10.1249/mss.0000000000002792
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Exercise Training on Lean Body Mass in Breast Cancer Patients: A Systematic Review and Meta-analysis

Abstract: Purpose: Reduced lean body mass (LBM) is common during and after treatment for breast cancer, and it is associated with increased treatment-induced toxicity, shorter time to tumor progression, and decreased survival. Exercise training is a potential intervention for maintaining or increasing LBM. We conducted a systematic review and a meta-analysis to investigate the effects of exercise training on LBM in breast cancer. Methods: A comprehensive search was performed to November 2020 for randomized controlled tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
(265 reference statements)
1
5
0
Order By: Relevance
“…The observed increases in lean mass following resistance exercise have clinical implications including counteracting treatment‐related side‐effects such as reducing the incidence of lymphedema, 64 preventing bone loss during hormone therapy, 47,49,50,56 and improving chemotherapy completion rate 57 . Our findings are supported by previous meta‐analyses that stress the importance of including resistance exercise as part of cancer treatment, not only to increase lean mass during and after treatment to help combat sarcopenia 143 but also to improve muscle strength, physical function and overall quality of life in this population 144–146 . More recently, we reported that increased lean mass was associated with increased levels of myokines (released at rest and in response to exercise) post‐exercise in men with advanced prostate cancer 147 .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The observed increases in lean mass following resistance exercise have clinical implications including counteracting treatment‐related side‐effects such as reducing the incidence of lymphedema, 64 preventing bone loss during hormone therapy, 47,49,50,56 and improving chemotherapy completion rate 57 . Our findings are supported by previous meta‐analyses that stress the importance of including resistance exercise as part of cancer treatment, not only to increase lean mass during and after treatment to help combat sarcopenia 143 but also to improve muscle strength, physical function and overall quality of life in this population 144–146 . More recently, we reported that increased lean mass was associated with increased levels of myokines (released at rest and in response to exercise) post‐exercise in men with advanced prostate cancer 147 .…”
Section: Discussionsupporting
confidence: 82%
“…There is evidence that excess fat and low lean mass (i.e., sarcopenic obesity) are common side‐effects during and after breast cancer treatment 22,141 and are more prevalent in older cancer patients 142 . In addition, sarcopenic obesity is also strongly associated with increased treatment toxicity 143 and decreased survival rate 15 . The observed increases in lean mass following resistance exercise have clinical implications including counteracting treatment‐related side‐effects such as reducing the incidence of lymphedema, 64 preventing bone loss during hormone therapy, 47,49,50,56 and improving chemotherapy completion rate 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, previous research showed similar effects of CART on various anthropometric and body composition indices among BC patients and survivors (Joaquim et al, 2022). Ultimately, exercise training is more beneficial than usual care for increasing FFM in women with BC, both during and after treatment (Fraser et al, 2022). Taking this into account, the present findings corroborate the current evidence underlining the vital role of regular exercise training, with particular emphasis on muscle strengthening activities, regarding the physiological and functional importance of FFM in this cohort (Fraser et al, 2022).…”
Section: Anthropometrics and Body Compositionmentioning
confidence: 57%
“…Most body composition parameters were decreased in the control and intervention groups, with no significant differences between the groups ( Table 3 ). Breast cancer treatment leads to an increase in adipose tissue and accelerates the loss of lean mass ( 3 ), and exercise during and after treatment can oppose these effects ( 15 ). We found no differences in lean or fat mass at any of the timepoints between the groups, likely due to our sample size and short-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of outcomes from randomized controlled trials of exercise interventions for patients with breast cancer between 2000 and 2018 reported that exercise interventions (usually 150 minutes per week of moderate to vigorous exercise) have a positive impact on QoL as well as CVD risk factors such as body fat, body mass index (BMI), and physical fitness ( 14 ). Lifestyle interventions can also prevent negative changes in body composition ( 15 ) and improve metabolic biomarkers and insulin resistance in overweight patients with breast cancer ( 16 ). Weight reductions, which are often associated with lifestyle interventions, can help normalize resting metabolic rates (RMR).…”
Section: Introductionmentioning
confidence: 99%